Obstetric and neonatal outcomes in pregnant women with anxiety disorders (Annals of Medical Research, 2025)
Aim: To examine the obstetric and neonatal prognoses of women with pregestational anxiety and contribute to maternal and neonatal health for pregnant women managing anxiety.Materials and Methods: This retrospective study included 60 women with singleton pregnancies aged between 18 and 45 years who presented to the Perinatology Clinic of Ankara City Hospital between January 1, 2021, and December 1, 2024, and were diagnosed with anxiety disorders in the psychiatry department of the same hospital during the prenatal period. We evaluated the demographic characteristics such as age and gravidity, and clinical factors such as obstetric complications, birth weight, first- and fifth-minute Apgar scores, and neonatal intensive care requirements.Results: The median age of pregnant women monitored for anxiety disorders was 31 years. Generalized anxiety disorder was the most common diagnosis among the anxiety disorders. Medical treatment was administered to 60% of the pregnant women. Of the patients diagnosed with anxiety disorders, 12 experienced preterm delivery. Five patients were diagnosed with hypertensive disorders of pregnancy, and one patient with substance-induced anxiety disorder underwent emergency delivery due to placental abruption. Fetal anomalies observed in the study group included cataract (n=1), microcephaly (n=1), ileal atresia (n=1), and agenesis of the corpus callosum(n=1) . Among newborns delivered by mothers with anxiety disorders, the median gestational age at birth was 38 weeks, and the median birth weight was 3000 grams.Conclusion: Anxiety disorders are associated with adverse obstetric outcomes, particularly preterm delivery.
Keywords: Anxiety; Panic disorder; Maternal factors; Fetal factors; Obstetrics; Fetal anomaly